2014
DOI: 10.1159/000354733
|View full text |Cite
|
Sign up to set email alerts
|

‘Scarless' Laparoscopic Urologic Surgery by the Combination of Mini-Laparoscopic and Laparoendoscopic Single-Site Surgery Equipment

Abstract: Objective: We evaluated reconstructive and oncological laparoendoscopic single-site surgery (LESS) combined with mini-laparoscopic instruments as standard equipment. Patients and Methods: 30 patients underwent reconstructive and oncological LESS: mini-laparoscopic-assisted LESS pyeloplasty (LESS-P, n = 18), mini-laparoscopic-assisted LESS partial nephrectomy (LESS-PN, n = 7) or mini-laparoscopic-assisted LESS radical prostatectomy (LESS-RP, n = 5). Perioperative data were prospectively collected. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Since LP started to get popularized within the last 2 decades, the surgical steps of the procedure have been the subject of numerous publications [6,7,8,9,10]. Of the surgical steps that affects the operative time and success, stenting is another critical step of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Since LP started to get popularized within the last 2 decades, the surgical steps of the procedure have been the subject of numerous publications [6,7,8,9,10]. Of the surgical steps that affects the operative time and success, stenting is another critical step of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Mini-laparoscopy also comprises thinner instruments of 3 mm size. Kallidonis et al [23] demonstrated that the routine addition of mini-laparoscopic instruments to LESS overcomes the challenges organ retraction and suturing. LESS combined with mini-laparoscopic instruments enables even complex procedures such as pyeloplasty, radical prostatectomy, and partial nephrectomy [23].…”
Section: Discussionmentioning
confidence: 99%